5‐Hydroxypyran‐4‐one derivatives as potential therapeutic iron–chelating agents. Issue 2 (22nd February 2016) - Li, Junpei; Abbate, Vincenzo; Jurach, Jagoda; Zhang, Guoqing; Kong, Xiaole; Hider, Robert C.
Abstract: Kojic acid can be condensed with amines via the Mannich reaction in good yield without protection of the phenolic group. Using this synthetic approach two tridentate chelators and a hexadentate chelator have been prepared. All three possess a high affinity for iron(III), a pFe value of 21.5 being associated with the hexadentate ligand which renders it a useful lead chelator for clinical application. The present work represents our interest in preparing and investigating kojic acid derivatives which might have some potential physiological activity. The huge advantages of these molecules are that they are easy and cheap to produce. Abstract : The pFe III value for3 is 21.5, the major species at pH 7.4 being FeL (1:1), which possesses a net charge of 1 ‐ . The ligand is hexacoordinate, the iron binding to the four phenolic functions and the two amino nitrogens, in similar fashion to EDTA.